Islet and Stem Cell Encapsulation for Clinical Transplantation - Krishnan, Rahul (Rev Diabet Stud, 2014)
Over the last decade, improvements in islet isolation techniques have made islet transplantation an option for a certain subset of patients with long-standing diabetes. Although islet transplants have shown improved graft function, adequate function beyond the second year has not yet been demonstrated, and patients still require immunosuppression to prevent rejection. Since allogeneic islet transplants have experienced some success, the next step is to improve graft function while eliminating the need for systemic immunosuppressive therapy. Biomaterial encapsulation offers a strategy to avoid the need for toxic immunosuppression while increasing the chances of graft function and survival. Encapsulation entails coating cells or tissue in a semipermeable biocompatible material that allows for the passage of nutrients, oxygen, and hormones while blocking immune cells and regulatory substances from recognizing and destroying the cell, thus avoiding the need for systemic immunosuppressive therapy. Despite advances in encapsulation technology, these developments have not yet been meaningfully translated into clinical islet transplantation, for which several factors are to blame, including graft hypoxia, host inflammatory response, fibrosis, improper choice of biomaterial type, lack of standard guidelines, and post-transplantation device failure. Several new approaches, such as the use of porcine islets, stem cells, development of prevascularized implants, islet nanocoating, and multilayer encapsulation, continue to generate intense scientific interest in this rapidly expanding field. This review provides a comprehensive update on islet and stem cell encapsulation as a treatment modality in type 1 diabetes, including a historical outlook as well as current and future research avenues.